Portrait of a juvenile cheetah, looking up from a Thompson’s gazelle caught by the nearby mother, in Serengeti National Park. - Kerr, Jeremy (Université d'Ottawa | University of Ottawa, 2019)
This juvenile cheetah has been eating a Thompson’s gazelle, and its face is a little bloody as a consequence. Four other young cheetahs were nearby, as was the mother. This family of cheetahs was large and appeared very healthy. Cheetahs can usually be found in the eastern Serengeti’s short grass plains, presumably because this habitat enables them to use their extraordinary speed more effectively for hunting.
Keywords: Field course; Africa; African Ecology; cheetah; Tanzania; Serengeti National Park; national park; OUPFB; Ontario Universities Program in Field Biology